PENINGKATAN KUALITAS EFLUEN LIMBAH CAIR INDUSTRI TAHU PADA SISTEM LUMPUR AKTIF DENGAN VARIASI LAJU ALIR MENGGUNAKAN ARANG AKTIF KAYU ULIN (Eusideroxylon zwageri) - Filomena Matilda; Danang Biyatmoko; Akhmad Rizali; Abdullah Abdullah (Universitas Lambung Mangkurat, 2016)
Tofu industry produces organic waste that can decrease the quality of the environment. The alternative processing method can be used among others is activated sludge system, but several types of research have not shown optimal results yet. To improve the quality of wastewater, the treatment of wastewater of tofu using activated charcoal needs to be done. The purpose of this research is to analyze the effects of the ironwood charcoal activation on the morphology and surface area of ironwood activated charcoal, to analyze the effects of variations in the flow rate of tofu wastewater effluent from activated sludge using ironwood activated charcoal on the parameters of temperature, pH, TSS, BOD, COD and ammonia and to find out the optimum flow rate of tofu wastewater effluent from activated sludge using ironwood activated charcoal. This research used adsorption method with column system at 7 treatments of flow rate (50, 60, 70, 80, 90, 100 and 110 mL/h) with 3 replications. The activation of ironwood charcoal used Na2CO3 5% and was activated at 400oC. The results showed that the surface morphology of ironwood active charcoal had more open pore surfaces with more regular structures than before activation. The surface area of ironwood activated charcoal was 32.936 m2/g and increased to 53.7% compared with it before activation. Variations in the flow rate on the tofu wastewater effluent from activated sludge using ironwood activated charcoal showed highly significant (p < 0.01) in reducing the levels of TSS, BOD, COD, and ammonia. The optimum flow rate obtained at 50 mL/h with temperature was 25.8oC, pH 8.08, TSS 34.7 mg/L, BOD 43.8 mg/L, COD 117 mg/L and ammonia 14.8 mg/L. The value of temperature, pH, TSS and BOD have fulfilled the quality standards, the quality of tofu wastewater effluent increased from the activated sludge.